2000
DOI: 10.1210/endo.141.9.7648
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Estrogens Directly Alter Androgen-Regulated Prostate Development*

Abstract: Neonatal exposure to high doses of estrogen results in permanent suppression of prostate growth and reduced sensitivity to androgens in adulthood. It is unclear whether alterations in prostate growth are due to a direct effect of estrogens on the gland or are the result of hypothalamic-pituitary-gonadal axis suppression and a subsequent reduction in androgen levels. Therefore, the aim of this study was to determine whether estrogens have a direct effect on the prostate using a defined method of culturing neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 27 publications
7
30
0
4
Order By: Relevance
“…As expected, mice lacking functional ERs develop prostatic phenotypes (recently reviewed by Jarred et al [62]). Obviously, because mice with prostate-targeted inactivation of ERs are not yet available, the phenotype is not necessarily caused solely by the lack of the receptor in prostatic tissue, but may also be secondary to the altered CNS-gonadal function.…”
Section: Er-deficient Mouse Modelssupporting
confidence: 63%
See 1 more Smart Citation
“…As expected, mice lacking functional ERs develop prostatic phenotypes (recently reviewed by Jarred et al [62]). Obviously, because mice with prostate-targeted inactivation of ERs are not yet available, the phenotype is not necessarily caused solely by the lack of the receptor in prostatic tissue, but may also be secondary to the altered CNS-gonadal function.…”
Section: Er-deficient Mouse Modelssupporting
confidence: 63%
“…It is well known that estrogen treatment induces development of squamous epithelial metaplasia in prostate, in particular at sites where the underlying stroma expresses ERā£. This does not occur in ERā£KO mouse, indicating that this specific response is ERā£-dependent [65,62] and likely to be mediated by prostatic ERā£. Squamous epithelial metaplasia has also been observed in human prostate, particularly in the posterior periurethral region (Fig.…”
Section: Er-deficient Mouse Modelsmentioning
confidence: 87%
“…ERā£ is expressed in both prostatic fibroblasts and smooth muscle cells (30,44). Administration of estrogens has been shown to influence both fibroblast and smooth muscle cell proliferation and differentiation (30,36). In the current studies, loss of ERā£ in the mouse prostate led to decreased fibroblast cell proliferation and content but increased smooth muscle cell content, which suggested that ERā£ could have a differential effect on the two types of stromal cells and potentially be involved in the remodeling of prostate stromal cellular composition.…”
Section: Discussionmentioning
confidence: 50%
“…Estrogen, primarily 17ā¤-estradiol (E2), has also been proposed to be involved in both normal and abnormal processes of male reproductive development and associated diseases (5,6). Male estrogen is synthesized by aromatization of androgen, (e.g.…”
Section: Androgen Action Via the Androgen Receptor (Ar)mentioning
confidence: 99%